A descriptive study to assess malnutrition among the preschool (3 to 5 years) children in rural community at wavanje village - Babu, Dhanraj (Indian Journal of Nursing Sciences, 2024)
Objective: To assess the nutritional status of children in age group between 3-5 years. Methodology: The descriptive survey study was conducted in the rural community of Wavanje village, Panvel, Distict Raigad, Maharashtra. Total 100 subjects were randomly selected. Data collection was done using a predesigned and pre-tested questionnaire. The participants were subjected to anthropometry (weight, height and Mid Upper Arm Circumference (MUAC)) measurements following standard technique. BMI and other parameters were also assessed; the data thus obtained and were analyzed. Results: It was observed that out of 100 subjects, 51 (53%) were male and 49 (47%) were female. The occupation statuses of parents were 25% in-service, 20% business, and remaining 55% were farmers and brick makers. The education status of parents: most of the fathers (28 %) were educated up to SSC and 18% were illiterate. Considering the mothers, 30% were illiterate and only 20% were educated up to eighth standard, which indicated that the lack of knowledge in child care and nutrition resulting in malnutrition. After analyzing the anthropometrical data, it was found that malnutrition was more prevalent among boys; belonging to the age of 5 years and in girls belonging to the age of 5 years as compared to the other children in the age group 3 to 5 years due to increase in the activities and reduced intake of nutrition that ultimate affects the growth and development. According to the Indian Academy of Pediatrics (IAP) classification the prevalence of Grade I malnutrition was 47.10%, Grade II was 20.50% and Grade III and IV were 32.40%). Conclusion: Most of the children were underweight and malnourished, well planned nutritional strategies to be made for school rehabilitation for prevention of malnutrition among school children.